A zero emission internal combustion engine with hydrogen/oxygen combustion for stationary energy storage applications - Link Thomas; Haller Johannes; Rahtje Rio (E3S Web of Conferences)
Renewable energies are considered a potential way to reduce the greenhouse gas emissions of the power supply system. To improve the baseload operation capability of a power supply system based on renewable energies hydrogen as energy storage for electrical energy is widely discussed. This research focuses on the reconversion of hydrogen to electrical energy using an internal combustion engine. The main point of interest is the question whether the combustion of hydrogen with oxygen instead of air offers advantages over a conventional use of hydrogen in an internal combustion engine. As a result, an alternative engine process for hydrogen utilisation in internal combustion engines employing hydrogen/oxygen combustion is presented. The process control is based on a ballast gas that regulates the combustion temperature. The ballast gas used is water vapor, which is fed into an external cycle after combustion. The concept is analysed using a quasi-dimensional model with a two-zone combustion approach. The results show that indicated efficiencies exceeding 50 % can be achieved, with high power density enabled by a two-stroke operation.